2018
DOI: 10.1007/s00277-018-3379-5
|View full text |Cite
|
Sign up to set email alerts
|

Brentuximab vedotin as salvage treatment in Hodgkin lymphoma naïve transplant patients or failing ASCT: the real life experience of Rete Ematologica Pugliese (REP)

Abstract: Brentuximab vedotin (BV) shows a high overall response rate (ORR) in relapsed/refractory (R/R) Hodgkin lymphoma (HL) after autologous transplant (ASCT). The aim of this multicenter study, conducted in nine Hematology Departments of Rete Ematologica Pugliese, was to retrospectively evaluate the efficacy and safety of BV as salvage therapy and as bridge regimen to ASCT or allogeneic transplant (alloSCT) in R/R HL patients. Seventy patients received BV. Forty-five patients (64%) were treated with BV as bridge to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 25 publications
1
6
0
Order By: Relevance
“…However responses appear short-lived, and only patients with a CR according to the criteria of the pivotal trial have a realistic chance of long-term survival [5]. Consolidation with a second, mostly allogeneic, SCT is advocated by some authors [13,21,22]. Our data support the use of consolidation and an allogeneic SCT following BV has been used more often since the introduction of BV.…”
Section: Discussionsupporting
confidence: 56%
See 3 more Smart Citations
“…However responses appear short-lived, and only patients with a CR according to the criteria of the pivotal trial have a realistic chance of long-term survival [5]. Consolidation with a second, mostly allogeneic, SCT is advocated by some authors [13,21,22]. Our data support the use of consolidation and an allogeneic SCT following BV has been used more often since the introduction of BV.…”
Section: Discussionsupporting
confidence: 56%
“…Observational data also support the use of BV in patients with r/r disease that do not respond adequately to salvage chemotherapy, but would otherwise be suitable for transplant [8,[11][12][13][14][15][16]. Few investigators have reported on the durability of responses thus consolidated.…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…Among 29 patients treated with BV as bridge to allogeneic transplantation, overall and CR rates were 62% and 24%, respectively, and 93% of them proceeded to transplantation. This and other real-life studies indicate that BV may allow for disease control before transplantation, potentially improving post-transplantation outcomes, also in refractory and heavily pretreated patients, with acceptable tolerability and no significant overlapping toxicities with prior therapies [88][89][90][91][92].…”
Section: Real-life Experience With Approved Novel Agentsmentioning
confidence: 96%